Infantile Hepatic Hemangioendothelioma Associated With Congestive Heart Failure: Two Case Reports With Different Outcomes. Issue 52 (December 2015) - Wang, Tao; Wang, Yibin; Liang, Yun; Lu, Guoyan
Abstract : Abstract: Infantile hepatic hemangioendothelioma (IHH) is rare which can regress spontaneously. Arteriovenous shunts within hemangiomas, however, may result in pulmonary artery hypertension (PAH) and congestive heart failure (CHF). The authors report 2 young infants suffering from multifocal IHH associated with CHF were both treated with glucocorticoid and transcatheter arterial embolization (TAE), but had different outcomes. The PAH decreased immediately and the symptoms of CHF were alleviated after TAE for both of them. For the Tibetan infant, the development was normal with tumor regression by follow-up. For the Han ethnic neonate, PAH increased again in the seventh day with progressive cardiovascular insufficiency. Ultrasound showed a persisting perfusion caused by collateralization around occluded main feeders. Furthermore, a pulmonary infection occurred and ventilation was performed. As a result, the infant died from multiorgan failure caused by CHF and infection. TAE is a treatment of reducing shunting for hemangiomas. Fistula recanalization in multifocal IHH, however, might be an important risk factor affecting the outcome of TAE. TAE should be further evaluated with special attention to anatomy of feeding and draining vessels, and cardiopulmonary conditions. In addition, the patients were susceptible to secondary pulmonary infection because of lung congestion. As well, the infant from the high altitude area showed better adaptability to hypoxia.